2008
DOI: 10.11646/zootaxa.1768.1.1
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of the land snail family Orthalicidae (Gastropoda: Pulmonata: Orthalicoidea) in Ecuador, with notes on the distribution of the mainland species

Abstract: The family Orthalicidae is wide-spread in the Neotropics and a major member of the land snail fauna of most South American countries. This checklist presents the species known to exist in Ecuador. It is based on data from relevant literature and museums world wide. There are 168 species in total, 63 of which occur on the Galápagos; 9 species are listed for the first time from this country. New synonymies are: Bulimus abscissus Pfeiffer, 1855 = Drymaeus (D.) fallax Pfe-iffer, 1853; Bulimus caliginosus Reeve, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 28 publications
0
30
1
6
Order By: Relevance
“…The collector, L. Peña, wrote two provinces for this locality: Carchi and Napo. Breure and Borrero (2008) indicated that there is a locality in Putumayo (Colombia) called Sibunday that has been often referred to as an Ecuadorian locality spelled Sebundoi. Sibunday, at 2,104 m in elevation, is close in distance to Napo and Carchi provinces and was possibly mistakenly placed in those northern Ecuadorian provinces in the case of these four specimens.…”
Section: Resultsmentioning
confidence: 99%
“…The collector, L. Peña, wrote two provinces for this locality: Carchi and Napo. Breure and Borrero (2008) indicated that there is a locality in Putumayo (Colombia) called Sibunday that has been often referred to as an Ecuadorian locality spelled Sebundoi. Sibunday, at 2,104 m in elevation, is close in distance to Napo and Carchi provinces and was possibly mistakenly placed in those northern Ecuadorian provinces in the case of these four specimens.…”
Section: Resultsmentioning
confidence: 99%
“…The methodology follows that used by Breure and Borrero (2008). Distributional data are given within the countries, arranged by main political divisions indicated in bold type, unless otherwise indicated; imprecise or untraceable locations are arranged under "?".…”
Section: Methodsmentioning
confidence: 99%
“…While orthalicoid snails occur and are quite diverse in the Galápagos Islands off Ecuador (viz. the genus Naesiotus, Breure & Borrero 2008), no species of Plekocheilus or Dryptus are known from these islands. A similar situation exists with the Colombian islands of San Andrés and Providencia in the Caribbean, from which species of Drymaeus, Bulimulus, and Orthalicus are known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neotropical overview of land snails is still poor in many countries (Régnier et al, 2015), highlighting the malacological studies performed in Argentina (Cuezzo et al, 2013), Brazil (Simone, 2006), Colombia (Linares & Vera, 2012), Cuba (Espinosa & Ortea, 2009), Ecuador (Breure & Borrero, 2008) and Peru (Breure & Avila, 2016). In Chile, the study of land snails has been focused especially in the description of new species (Araya & Aliaga, 2015;Miquel & Araya, 2013Valdovinos & Stuardo, 1988; as well as studying their distributional range and reporting new records of exotic species (Araya, 2015a(Araya, , b, 2016Araya & Catalán, 2014;Araya et al, , 2017Cádiz & Gallardo, 2007;Martínez-de los Ríos, 2017;Stuardo & Vega, 1985;Valdovinos, 1999;Valdovinos & Stuardo, 1989).…”
Section: Introductionmentioning
confidence: 99%